EFEKTIVITAS PENGGUNAAN WHATSAPP SEBAGAI MEDIA KOMUNIKASI ORGANISASI DI LINGKUNGAN PEGAWAI DINAS ATR/BPN KOTA PALEMBANG - Yahya, Achmad; Dirgantara, Pradipta (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
Based of Internet world stat that in 2021 internet users reached 212,35 million and in position 15 in all of asia and always be growing. The one that really many people use in internet is social media Whatsapp. Whatsapp has been used in many corporate or office for the organizational communication. Researcher curious how Whatsapp can help workers to do organizational communication in ATR/BPN Palembang region. The purpose of this research is to find the effectiveness of using Whatsapp for organizational communication in ATR/BPN Palembang region. The method of this research is quantitative descriptive. The sample is 61 worker in ATR/BPN Palembang region with probability sampling. Researched found that Whatsapp effective for fulfilling the organizational communication with score 3,04 dan continum line between 2,50-3,25 and with the highest aspect of communal and the lowest aspect of duty.